Assessment of sheep oocyte quality for in vitro maturation - RANGASAMY, S; KULASEKAR, K; BALASUBRAMANIAN, S; DHINAKAR RAJ, G (The Indian Journal of Animal Reproduction, 2023)
Sheep ovaries were collected from slaughter house and transported to the laboratory within 30 min. A total of 2117 oocytes were retrieved using slicing technique with a rec very rate of 4.9 l oocytes per ovary. Among the collected oocytes 33.87 (717), 32.73 (693) and 33.40 (707) per cent of oocytes were graded as A, B and C, respectively. The mean maturation percentage of A, Band C grade oocytes in the present study was 95.48 ± 0.63, 89.14 ± 1.17 and 77.94 ± 1.12, respectively. The maturation rate of A grade oocytes were significantly (<0.01) higher than that ofB and C grades and B grade oocytes were significantly (<0.01) higher than that ofC grade oocytes. The overall maturation rate of oocytes in the present study was 7.5 ± 1.08 per cent.